PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA TEKA TEKI SILANG (TTS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS VI SD NEGERI PAJURANGAN - Ajunaida Kurniawati; Ludfi Arya Wardana; Shofia Hattarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this study is to examine the implementation and improvement of students’ critical thinking skills in the IPAS subject through the Problem-Based Learning (PBL) model assisted by crossword puzzle at SD Negeri Pajurangan. This research uses a Classroom Action Research (CAR) method following the Kemmis and McTaggart model, conducted over two cycles. Each cycle consisted of two meetings and followed four stages: planning, action, observation, and reflection. The research subjects were 21 sixth-grade students at SDN Pajurangan, consisting of 7 male students and 14 female students. Data collection techniques included observation, tests, and documentation. The results showed that in Cycle I, only 13 students achieved the minimum mastery criteria, representing 61.90%, with an average score of 67.14. Meanwhile, the average score for critical thinking skills was 48.38. In Cycle II, the number of students who met the criteria increased to 18, or 85.71%, with a class average of 82.61, and the average critical thinking score improved significantly to 80.76. These results indicate an overall improvement in both learning outcomes and critical thinking skills, meeting the classical completeness threshold set by the researcher at 70%.